The Predictive Value of Pretreatment Lactate Dehydrogenase and Derived Neutrophil-to-Lymphocyte Ratio in Advanced Non-Small Cell Lung Cancer Patients Treated With PD-1/PD-L1 Inhibitors: A Meta-Analysis - Zhang, Qianning; Gong, Xiaoling; Sun, Lei; Miao, Liyun; Zhou, Yujie (Frontiers in Oncology, 2022)
Background: The Lung immune prognostic index(LIPI) consists of lactate dehydrogenase(LDH) and derived neutrophil-to-lymphocyte ratio(dNLR). Many studies have shown LDH and dNLR are associated with prognosis of advanced non-small-cell lung cancer(NSCLC) in patients treated with programmed death cell protein-1(PD-1) or programmed death cell protein ligand-1(PD-L1) inhibitors. However, previous results are inconsistent and the conclusion remains unclear. This meta-analysis aims to investigate the predictive value of pretreatment LDH and dNLR for NSCLC progression in patients treated with PD-1/PD-L1 inhibitors. Methods: PubMed, Embase, and the Cochrane Library were searched by two researchers independently for related literature before March 2020. The hazard ratio (HR) with a 95% confidence interval (CI) for the progression-free survival (PFS) and overall survival (OS) were extracted to assess the predictive value of LDH and dNLR. STATA 15. 0 was used to perform the meta-analysis. Results:3429 patients from 26 studies were included in this meta-analysis. The results revealed that high pretreatment LDH was related to poor OS(HR=1.19, 95% CI:1.11-1. 24, p＜0.001), but not closely related with poor PFS(HR = 1. 02, 95% CI: 1. 00–1. 04, p = 0. 023＜0. 05). The pooled results of dNLR suggested that high pretreatment dNLR was related with poor OS(HR=1. 55, 95% CI:1. 33–1. 80, P < 0. 001) and PFS(HR=1.33, 95% CI: 1.16–1. 54, P < 0.001). Conclusion: Both pretreatment LDH and dNLR have the potential to serve as the peripheral blood biomarkers for advanced NSCLC patients treated with PD-1/PD-L1 inhibitors. However, more studies on LDH are needed to evaluate its predictive value for PFS in NSCLC patients.